(untitled) (Journal of Accessibility and Design for All, 2024)
Amidst the global COVID-19 pandemic, strict lockdown measures were implemented worldwide to safeguard lives and limit widespread infections. Accordingly, distance learning methods were implemented at educational institutions. This paper critically examines the adaptation of distance learning methods for university students during this crisis, arguing that insufficient attention was given to mental health and mental and emotional well-being. The situation’s urgency led to overlooking psychological factors that subsequently impacted students’ learning outcomes and academic performance, especially when compared to traditional learning experiences. This paper focuses on architecture students at the University of Jordan, aiming to reveal to what extent the implementation of distance learning during the COVID-19 lockdown affected their mental health and psychological well-being, thus affecting their overall performance. Using a mixed-method approach, the paper included real-time class observation, reflection exercises conducted during the lockdown, and a survey distributed to architecture undergraduates. The survey aimed to increase our understanding of the intricate connections between mental health, psychological well-being, and the dynamics of online educational environments, thus providing insights for future online learning scenarios. The paper’s findings exposed overlooked dimensions during the rapid transition to online learning. The emphasis on technical aspects such as infrastructure, devices, and software side-tracked the end-users importance and performance within the educational process. Concepts like ’toxic positivity,’ intensified by increased social media usage during the lockdown, gained prominence. By examining the impact on architecture students in Jordan, this paper underscores key findings, identifies critical issues, and advocates for a more comprehensive approach to distance learning.